Platformisation in game development - Aleena Chia; Brendan Keogh; Dale Leorke; Benjamin Nicoll (Internet Policy Review, 2020)
This article examines how the process of platformisation is manifesting in videogame development. Rather than reinforcing a top-down perspective of platformisation centred on distribution platforms like app stores, we focus on often overlooked game-making tools and the independent, entrepreneurial, and fringe communities that govern and use them. We draw on case studies of Unity and Twine, two such tools that have transformed videogame creation and distribution. By considering how they complicate existing understandings and definitions of both 'platform' and 'platformisation', we move beyond reductive narratives that frame platformisation as a fixed, hegemonic process. Instead, we reveal a much more ambiguous and complex relationship between game makers and the platforms they use.
Keywords: 300; Cultural production; Democratisation; Game engines; Game development; Platformisation; Platforms